PERIODIC WAVE SOLUTIONS FOR THE GENERALIZED SHALLOW WATER WAVE EQUATION BY THE IMPROVED JACOBI ELLIPTIC FUNCTION METHOD - İnç, Mustafa; Ergut, Mahmut (Tsing Hua Univ, Dept Mathematics, 2005)
In this paper, improved Jacobi elliptic function method is used to construct new exact doubly periodic wave solutions of the generalized shallow water wave equation (GSWW). The method can also be applied to other nonlinear partial differential equations (PDEs) or systems in mathematical physics.